Assessment of the impact of climate change on urban flooding: A case study of Beijing, China. Issue 10 (6th October 2022) - Ding, XingChen; Liao, WeiHong; Lei, XiaoHui; Wang, Hao; Yang, JiaLi; Wang, Hao
Abstract: Global climate change and rapid urbanization increase the risk of urban flooding, especially in China. Climate change and the 'heat island effect' have increased the frequency of extreme precipitation. Affected by the backwardness of drainage facilities and the lack of drainage capacity, many cities have experienced large-scale waterlogging in low-lying areas, and ocean-like phenomena appear in cities. The public infrastructure was damaged and caused a lot of economic losses. Therefore, it is important to investigate the adaptability of drainage systems to the future in a changing environment. The Sixth International Coupled Model Intercomparison Project (CMIP6) and Storm Water Management Model (SWMM) were used to quantify the impact of climate change on Beijing's waterlogging under different rainstorm scenarios for the future 40 years. The quantile delta mapping method of daily precipitation based on frequency (DFQDM) is proposed to correct the daily precipitation of the climate model and which is proved to be feasible. After the annual precipitation and extreme precipitation index are corrected, percent bias (PBIAS) is significantly reduced. The PBIAS of the extreme precipitation index of the corrected model is all controlled within 6%. The corrected accuracy of CanESM5 is the best. The total flood volume (TFV) of the node increases with the aggravation of climate change. The TFV of SSP5-8.5 and SSP2-4.5 increased by 45.43 and 20.8% in the 100-year return period, respectively, and more than 94% of the conduits reached the maximum drainage capacity in different return periods. After the low impact development (LID) was installed, the improvement effect on the outflow with a smaller return period was significant, decreasing by about 50%. The LID can effectively reduce the overflow of the drainage system. The results of this study can provide suggestions for the reconstruction of the drainage system and the management of flood risk for Beijing in the future. HIGHLIGHTS: The DFQDM method for daily precipitation correction of the climate model is proposed. The TFV of SSP5-8.5 and SSP2-4.5 increased by 45.43 and 20.8% in the 100-year return period, respectively. The LID can effectively reduce the overflow of the drainage system. Graphical Abstract